ANALISIS KARAKTERISTIK PASAR SENIOR LIVING D’KHAYANGAN JABABEKA, CIKARANG - Bertharia Nadya Pricillia; Priyendiswara A.B. Priyendiswara; Liong Ju Tjung (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
The number of elderly people in Indonesia, based on data from the Central Statistics Agency (BPS) in 2017 has reached 23.4 million or 8.97%. With a variety of data that shows a high level of elderly people in Indonesia, housing that supports the comfort, safety and health of the elderly is quite needed. The occupancy of the elderly in Jabodetabek is in fact already available but has not filled the demand. The purpose and objective of this study is to analyze market characteristics which consist of profiles of elderly people who are interested in living in senior housing, market capabilities, available supply ofsenior housing, number of requests forsenior housing, and determination of appropriate rental prices. The object study is Senior Living D’Khayangan Jababeka which located in Cikarang, Bekasi Regency. The research method used in data collection is field surveys, questionnaires and interviews with related parties. The analysis used is the analysis of the object of benchmarking and market. The output of this analysis is the determination of rental prices that match the market characteristics of senior housing and can be viable social-based properties in terms of markets. AbstrakJumlah lansia di Indonesia, berdasarkan data Badan Pusat Statistik (BPS) tahun 2017 telah mencapai 23,4 juta atau 8,97%. Dengan berbagai data yang menunjukkan tingkat lansia yang tinggi di Indonesia, hunian yang mendukung kenyamanan, keamanan dan kesehatan para lansia sangat dibutuhkan. Hunian lansia di Jabodetabek pada kenyataannya sudah tersedia namun belum memenuhi permintaan yang ada. Maksud dan tujuan studi ini adalah melakukan analisis karakteristik pasar yang terdiri dari profil lansia yang berminat tinggal di rumah lansia, kemampuan pasar, pasokan rumah lansia yang tersedia, jumlah permintaan rumah lansia, dan penentuan harga sewa yang tepat. Adapun objek studi yang diteliti yaitu Senior Living D’Khayangan Jababeka yang berlokasi di Cikarang, Kabupaten Bekasi. Metode penelitian yang digunakan dalam pengumpulan data yaitu survey lapangan, penyebaran kuesioner dan wawancara terhadap pihak terkait. Analisis yang dipakai ialah analisis objek studi pembanding (benchmarking) dan pasar. Output dari analisis ini adalah penentuan harga sewa yang sesuai karakteristik pasar dari rumah lansia dan dapat menjadi properti berbasis sosial yang layak dalam segi pasar.